Intra‐abdominal lymph node flaps in lymphedema therapy: An anatomical guide to donor site selection. Issue 2 (11th October 2021) - Daniel, Bassem W.; Sonnenberg, Anna M.; Stern, Josef E.; Tannapfel, Andrea; Yamamoto, Takumi; Ring, Andrej
Abstract: Background: Secondary lymphedema is a leading sequela of cancer surgery and radiotherapy. The microsurgical transfer of lymph node flaps (LNFs) to affected limbs can improve the symptoms. The intra‐abdominal cavity contains an abundant heterogenic source. The aim of this study is to aid selection among intra‐abdominal LNFs. Methods: Eight LNFs were harvested in a microsurgical fashion at five sites in 16 cadavers: gastroepiploic, jejunal, ileal, ileocolic, and appendicular. These flaps were compared regarding size, weight, arterial diameter, and lymph node (LN) count after histologic verification. Results: One hundred and sixteen flaps were harvested. The exposed area correlated with the flap weight and volume ( r 2  = 0.86, r  = 0.9). While gastroepiploic LNFs (geLNFs) showed the highest median weight of 99 ml, the jejunal LNFs (jLNFs) had the highest density with 3.8 LNs per 10 ml. The most reliable jLNF was 60 cm from the ligament of Treitz. Three or more LNs were contained in 94% of the jejunal, 88% of the ileal/ileocolic, and 63% of the omental LNs. The ileocolic LNF had the largest arterial diameter of 3 mm, yet the smallest volume. Conclusions: jLNF and ileal LNF provide a reliable, high LN density for simultaneous, smaller recipient sites. geLNFs are more suitable for larger recipient sites.